Actual cash financing situation of SMEs in Romania and further recommendations - Tonis (Bucea-Manea), Rocsana; Bucea-Manea-Tonis, Radu (Journal of Economic Development, Environment and People, 2014)
The world is experiencing a revolution in the digital and mobile technologies, with more information available more quickly and for more media than ever before. In this context, SMEs can turn to cloud solution. Although the advantages of using the cloud are compelling for SMEs still involves financial costs. In Romania the rate of access to funds is very low. In this context, SMEs need additional assistance to obtain funding.